Cardiovascular prevention in 50-year-old adults: an Italian intervention study. Issue 8 (August 2018) - Bordin, Paolo; Picco, Francesca; Valent, Francesca; Mattiussi, Bruna; Vidotto, Luigino; Brianti, Giorgio
Abstract : Aims: Cardio50 is a project of active risk identification and cardiovascular prevention implemented in an Italian cohort of healthy people aged 50. Methods: A total of 3127 individuals were invited for a screening visit with lifestyle interview and registration of BMI, blood pressure (BP), glucose, cholesterol and classified into groups: A (normal), B (abnormal lifestyle, normal parameters), C (at least one abnormal parameter). People in group C were offered a free blood test and a specialistic medical visit to investigate the suspect of hypertension, dyslipidemia or dysglycemia. Those in groups B and C were scheduled for a follow-up visit after 4–6 months and finally readdressed to the general practitioner. Results: A total of 2325 invited individuals attended the screening visit: 18% were classified in group A, 32% in B, 42% in C, 8% met exclusion criteria and were not classifiable. In group C, 86% attended to the cardiologist visit, 76% had dyslipidemia, 35% hypertension, 1% diabetes, 14% impaired fasting glycemia, 19% obesity, 21% metabolic syndrome; 21% were smokers, 11% at risk of alcoholism. At follow-up, we appreciated a decrease in BP in group C individuals. After lifestyle intervention, physical activity increased, whereas metabolic syndrome, impaired fasting glucose and risky drinking decreased. Conclusion: The current project is coherent with modern strategies based on multifactorial actions. After the intervention, we observed an early reduction in BP and some improvements in lifestyle. This simple and low-technology program allowed us to detect and treat large numbers of individuals at high risk for cardiovascular events.